Dark matter self-interactions in the matter power spectrum. Issue 7 (1st July 2022) - Garani, Raghuveer; Redi, Michele; Tesi, Andrea
Abstract: We study the imprints of secluded dark sectors with a mass gap and self-interactions on the matter power spectrum. When Dark Matter (DM) is sufficiently light, in the ballpark of a few KeV, and self-interacting we find qualitative difference with respect to ΛCDM and also to free streaming DM. In order to emphasize the role of interactions for the evolution of the primordial perturbations we discuss various regimes: ranging from the ideal case of a tightly coupled perfect fluid to the free case of Warm Dark Matter, including the realistic case of small but non-vanishing self-interactions. We compute the matter power spectrum in all these regimes with the aid of Boltzmann solvers. Light dark sectors with self-interactions are efficiently constrained by Lyman- α data and we find that the presence of self-interactions relaxes the bound on the DM mass. As a concrete realization we study models with dark QCD-like sectors, where DM is made of light dark-pions.